2008
DOI: 10.1177/154405910808700409
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Representation Area of Human Dental Pulp

Abstract: To elucidate the dental pulp-representing area in the human primary somatosensory cortex and the presence of A-beta fibers in dental pulp, we recorded somatosensory-evoked magnetic fields from the cortex in seven healthy persons using magnetoencephalography. Following non-painful electrical stimulation of the right maxillary first premolar dental pulp, short latency (27 ms) cortical responses on the magnetic waveforms were observed. However, no response was seen when stimulation was applied to pulpless teeth, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 36 publications
2
18
0
Order By: Relevance
“…This is in agreement with earlier findings based on recording somatosensory-evoked magnetic fields during intraoral tactile stimulation (excluding the teeth) in humans (Tamura et al 2008) and from neuronal tracing studies (teeth and tongue) in new world monkeys (Iyengar et al 2007). Previous studies have reported locations in the SI cortex for intraoral structures including the lip, hard palate, gingiva, and tongue (Murayama et al 2005;Nakahara et al 2004;Nevalainen et al 2006), tooth dental pulp (Kubo et al 2008), and tooth tactile stimulation (Miyamoto et al 2006), but this is the first report of SI activations to psychophysically controlled vibrotactile stimulation of periodontal afferents.…”
Section: Brain Activation To 20 Hz Tooth Vibrationmentioning
confidence: 71%
“…This is in agreement with earlier findings based on recording somatosensory-evoked magnetic fields during intraoral tactile stimulation (excluding the teeth) in humans (Tamura et al 2008) and from neuronal tracing studies (teeth and tongue) in new world monkeys (Iyengar et al 2007). Previous studies have reported locations in the SI cortex for intraoral structures including the lip, hard palate, gingiva, and tongue (Murayama et al 2005;Nakahara et al 2004;Nevalainen et al 2006), tooth dental pulp (Kubo et al 2008), and tooth tactile stimulation (Miyamoto et al 2006), but this is the first report of SI activations to psychophysically controlled vibrotactile stimulation of periodontal afferents.…”
Section: Brain Activation To 20 Hz Tooth Vibrationmentioning
confidence: 71%
“…These electroreceptors are densely distributed in the perioral region . In monotremes, bill skin electroreceptors are innervated by the trigeminal nerve, and signals from both are processed in the somatosensory neocortex of the forebrain (Pettigrew, 1999;Kubo et al, 2008), a characteristic evident in teeth. Electroreceptors and teeth show similar ontogeny with a dependency on cranial neural crest for the formation of both organs (Chai et al, 2000;Freitas et al, 2006).…”
Section: Remarks On the Evolution Of Dentitionmentioning
confidence: 99%
“…Nakahara et al using MEG showed S1 represented separate cortical areas for lips and tongue, with no clear separate area for gingiva [157]. Kubo et al used electrical stimulation on tooth pulp and recorded the results with MEG [158]. MEG was also used by Bessho et al for studing three separate areas in hard palate [159] etc.…”
Section: Magnetoencephalography (Meg)mentioning
confidence: 99%